2011
DOI: 10.4021/jem61e
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Patients With Ankylosing Spondylitis

Abstract: Background: The objective of this study is to investigate the presence of metabolic syndrome (MS) in patients with ankylosing spondylitis (AS) and to evaluate its relationship with the clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Certain studies point to the relationship between the metabolic syndrome and the inflammation [10,11]. It has been reported that the prevalence of MS is significantly increased in patients with inflammatory diseases like rheumatoid arthritis, psoriasis or AS than in the general population [12][13][14][15][16][17]. There is still little information regarding the prevalence of MetS in patients with AS.…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies point to the relationship between the metabolic syndrome and the inflammation [10,11]. It has been reported that the prevalence of MS is significantly increased in patients with inflammatory diseases like rheumatoid arthritis, psoriasis or AS than in the general population [12][13][14][15][16][17]. There is still little information regarding the prevalence of MetS in patients with AS.…”
Section: Introductionmentioning
confidence: 99%